Improving second-grade senior high-school students’ speaking skills by using Instagram - Ahmad, Mahdi; Jumaela, Yulia Faniarti (Jurnal Langua, 2024)
Reading is a crucial skill that students need to develop. Through reading, students gain knowledge and improve their language skills. This study aims to identify the strategies used by the English teacher in teaching narrative texts and to explore the students’ responses to these strategies among the tenth graders of MA Darul Ulum Sasa. We used a descriptive qualitative approach for this study. To collect data, we used observation, questionnaires, and documentation. The data was analyzed in three steps: Data Reduction, Data Display, and Drawing Conclusions or Verification. Our focus was on the English teacher and 27 tenth-grade students at MA Darul Ulum Sasa. The results showed that the English teacher used several techniques, such as defining the purpose of reading, silent reading, Question-Answer Relationship (QAR), vocabulary analysis, and discussion strategies. By using these methods, the teacher was able to try different ways of teaching reading based on the subject. As a result, the teaching techniques became more engaging and effective in helping students improve their ability to read narrative texts.